DEFINITION OF THE ESSENTIAL CHARACTERISTICS, CONTENT AND CATEGORIES OF THE ECONOMIC GLOBALIZATION PROCESS - V. B. Vaks (Russian Journal of Economics and Law)
The article presents a complex analysis of the globalization process content, notes the sufficient aspects of the researched process, analyzes the definitions of globalizations given by the Russian and foreign authors. The globalization content and specifics are revealed through the functioning of transnational corporations which act as a result and the main participant of globalization process. Conclusions are made concerning the role of the Russian economy in the mentioned process.